Alleviating impact of hydroethanolic Murraya koenigii leaves extract on bisphenol A instigated testicular lethality and apoptosis in mice. (8th January 2020) - Kaur, Sarvnarinder; Singh, Gurkirat; Sadwal, Shilpa; Aniqa, Aniqa
Abstract: Bisphenol A (BPA) is a well‐known endocrine disruptor that imposees adverse effects on male fertility via interacting with germ cells of testis. Objectives of present study were to investigate the possible protective effects of hydroethanolic Murraya koenigii leaves extract (HEMKLE) against BPA‐induced testicular damage and apoptosis in mice. Male Balb/c mice were divided into four different groups: Group I (control), Group II (HEMKLE), Group III (BPA) and Group IV (HEMKLE + BPA). Group III (BPA) showed significant decrease in sperm parameters, germ cell number along with increased lipid peroxidation (LPO) and reactive oxygen species (ROS). A significant decrease in antioxidant enzymes activity was also observed in Group III (BPA) animals. mRNA expression study revealed significant decrease in the expression of Bcl‐2 and increase in expressions of caspase‐9 and caspase‐3, thus clearly demonstrate BPA‐induced apoptosis. In addition, HEMKLE co‐administration to BPA‐treated mice showed a significant increase in sperm parameters, germ cell number, decreased levels of LPO and ROS, increased antioxidant enzymes activity in Group IV (HEMKLE + BPA). Also, mRNA expression study showed a significant increase in Bcl‐2 and decrease in caspase‐9 and caspase‐3 gene expressions in Group IV (HEMKLE + BPA). Thus, the present study suggests that HEMKLE intervention provides protection against BPA‐induced oxidative stress and apoptosis.